Effect of silver on the phase transition and wettability of titanium oxide films - Mosquera, Adolfo A.; Albella, Jose M.; Navarro, Violeta; Bhattacharyya, Debabrata; Endrino, José L. (Nature Publishing Group, 2016)
The effect of silver on the phase transition and microstructure of titanium oxide films grown by pulsed cathodic arc had been investigated by XRD, SEM and Raman spectroscopy. Following successive thermal annealing up to 1000 °C, microstructural analysis of annealed Ag-TiO2 films reveals that the incorporation of Ag nanoparticles strongly affects the transition temperature from the initial metastable amorphous phase to anatase and stable rutile phase. An increase of silver content into TiO2 matrix inhibits the amorphous to anatase phase transition, raising its temperature boundary and, simultaneously reduces the transition temperature to promote rutile structure at lower value of 600 °C. The results are interpreted in terms of the steric effects produced by agglomeration of Ag atoms into larger clusters following annealing which hinders diffusion of Ti and O ions for anatase formation and constrains the volume available for the anatase lattice, thus disrupting its structure to form rutile phase. The effect of silver on the optical and wetting properties of TiO2 was evaluated to demonstrate its improved photocatalytic performance.